Effect of stirrup corrosion on the shear strength of reinforced concrete short beams - El-Sayed, Ahmed K.; Hussain, Raja R.; Shuraim, Ahmed B. (Journal of Civil Engineering and Management, 2016)
The effect of stirrups damage due to corrosion on the shear strength and behaviour of reinforced concrete beams was experimentally investigated. A total of fourteen full-scale reinforced concrete beams were constructed and tested under four-point bending up to failure. The test beams were 200 mm wide, 350 mm deep, and 2800 mm long. The reinforcing stirrups of nine of the beams were subjected to accelerated corrosion prior to structural testing. The test variables were the corrosion damage level, spacing of stirrups, and shear span to depth ratio. The beams were tested under shear span to depth ratio of 2 or 1 representing short or deep members. The test results indicated that the corroded beams exhibited degradation in stiffness and shear strength in comparison to the uncorroded control specimens. This degradation appeared to increase as the corrosion level increases and as stirrup spacing as well as shear span to depth ratio decreases.First published online: 24 Aug 2015